A Full Compositional Range for a (Ga1‐xZnx)(N1‐xOx) Nanostructure: High Efficiency for Overall Water Splitting and Optical Properties. Issue 7 (8th October 2014) - Li, Yaguang; Zhu, Liping; Yang, Yefeng; Song, Hui; Lou, Zirui; Guo, Yanmin; Ye, Zhizhen
<x xml:space="preserve">Abstract</x> Bulk (Ga1‐xZnx)(N1‐xOx) as a photocatalyst has received increasing attention as a potential solution for the energy shortage challenge; however, its catalytic performance is highly limited by its bulk form. To improve the photochemical potential, the nanoscale form of this multiple‐metal oxynitrides is desirable. In this work, a new type of (Ga1‐xZnx)(N1‐xOx) nanostructure is obtained. Its composition can tuned to the full range (0.18 < x < 0.95). The (Ga1‐xZnx)(N1‐xOx) nanostructure exhibits excellent photocatalytic activity for overall water splitting, and the highest quantum efficiency of (Ga1‐xZnx)(N1‐xOx) is as high as 17.3% under visible light irradiation. Using this new type of (Ga1‐xZnx)(N1‐xOx) nanostructure, the narrowing of the bandgap for (Ga1‐xZnx)(N1‐xOx) is not only due to an increase in the valence band maximum, but it is also related to a decrease in the conduction band minimum.